دور التدريب في تحسين اداء العاملين - رياص, بالخير; أكرم, العايب; إلياس, عماري (University of eloued جامعة الوادي, 2020)
"تهدف هذه الدراسة إلى التعرف على دور التدريب في تحسين أداء العاملين داخل المؤسسات بالإضافة إلى تحسين سيرورة العمل، حيث كان الجانب التطبيقي لهذه الدراسة على مستوى مؤسسة شركة سونلغاز بالوادي، حيث اعتمدنا في دراستنا على المنهج الوصفي التحليلي في جمع المعطيات والبيانات المتعلقة بظاهرة موضوع البحث. ولتحقيق هذا الهدف استخدمنا الاستبيان كـأداة للدراسة وتم توزيع 40 استمارة للاستبيان داخل المؤسسة وقد اعتمدنا في تحليل بيانات الاستبيانات على برنامج الحزمة الاحصائية للعلوم الاجتماعية (SPSS)، ولاختبار الفرضيات الموضوعة استخدمنا المتوسطات الحسابية، الانحراف المعياري، اختبار تحليل التباين الأحادي، بالإضافة إلى استخدام أساليب تحليل الانحدار والارتباط وذلك لإثبات وجود علاقة بين متغيرات الدراسة. وفي الأخير خلصت الدراسة بأن التدريب هدفه تحسين كفاءة العامل داخل المؤسسة وضمان سيرورة حسنة لعمل المؤسسة وتحقيق أهداف المؤسسة بدون أدنى العواقب، بالإضافة إلى إزالة بعض جوانب الضعف والقصور في أداء العاملين وتحسين سلوكياتهم وانضباطهم بدرجة كبيرة، لأن العامل يعتبر المحرك الرئيسي للمؤسسة والتدريب يعتبر الركيزة الأساسية في تطوير وترشيد أداء القوى العاملة ""This study aims to identify the role of training in improving the performance of workers inside the institutions in addition to improving the process of work، where the applied aspect of this study was at the level of the Sonelgaz Company in the Valley، where we relied on our study on the descriptive analytical approach in collecting data and data related to the phenomenon of the research topic. To achieve this goal، we used the questionnaire as a study tool and 40 questionnaires were distributed within the institution. We adopted in the analysis of questionnaires data on the Statistical Package for Social Sciences (SPSS) program، and to test the hypotheses we used the arithmetic mean، the standard deviation، the test of mono-variance analysis، in addition to the use of methods of analysis Regression and correlation، to demonstrate a relationship between study variables. Finally، the study concluded that the training aims to improve the efficiency of the worker within the organization and ensure a good process for the work of the institution and achieve the goals of the institution without the slightest consequences، in addition to removing some aspects of weakness and deficiencies in the performance of workers and improving their behavior and discipline significantly، because the worker is the main driver of the institution and training is the main pillar In developing and rationalizing the performance of the workforce. "
مذكرة ماستر ادارة اعمال
Keywords: التدريب، أداء العاملين، التمكين الإداري، مجتمع العينة، التدريب الالكتروني; ..Key words: Training, employee performance, administrative empowerment, and the sample community, Electronic training